A new approach to design median control charts for location monitoring. Issue 7 (3rd July 2022) - Hussain, Shahid; Mahmood, Tahir; Riaz, Muhammad; Nazir, Hafiz Zafar
Abstract: In SPC, the most effective and magnificent tool is the control chart. The structure of control charting schemes required the assumption that the process is free from disturbances with known parameters or correctly estimated from the in-control process. These assumptions need to full fill for monitoring location parameter with mean control charts. But in practical, these assumptions are not always true, due to occasionally presence of outliers. That is why the median is a suitable measure as compared to the mean in the presence of disturbances. The ranked and neoteric ranked set samplings are suggested in this study to monitor the location parameter of the process by using median estimator for CUSUM, EWMA and Shewhart type control charts. The run-length profile is used as a performance measure for proposed median based control charts. The results reveal that for median control charts based on neoteric ranked set sampling scheme yield excellent outcomes. The real-life application is provided of the new charting schemes.